In vivo screening reveals interactions between Drosophila Manf and genes involved in the mitochondria and the ubiquinone synthesis pathway - Lindström, Riitta (BMC Genet, 2017)
BACKGROUND: Mesencephalic Astrocyte-derived Neurotrophic Factor (MANF) and Cerebral Dopamine Neurotrophic Factor (CDNF) form an evolutionarily conserved family of neurotrophic factors. Orthologues for MANF/CDNF are the only neurotrophic factors as yet identified in invertebrates with conserved amino acid sequence. Previous studies indicate that mammalian MANF and CDNF support and protect brain dopaminergic system in non-cell-autonomous manner. However, MANF has also been shown to function intracellularly in the endoplasmic reticulum. To date, the knowledge on the interacting partners of MANF/CDNF and signaling pathways they activate is rudimentary. Here, we have employed the Drosophila genetics to screen for potential interaction partners of Drosophila Manf (DmManf) in vivo. RESULTS: We first show that DmManf plays a role in the development of Drosophila wing. We exploited this function by using Drosophila UAS-RNAi lines and discovered novel genetic interactions of DmManf with genes known to function in the mitochondria. We also found evidence of an interaction between DmManf and the Drosophila homologue encoding Ku70, the closest structural homologue of SAP domain of mammalian MANF. CONCLUSIONS: In addition to the previously known functions of MANF/CDNF protein family, DmManf also interacts with mitochondria-related genes. Our data supports the functional importance of these evolutionarily significant proteins and provides new insights for the future studies. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12863-017-0509-3) contains supplementary material, which is available to authorized users.